Binder’s syndrome: a rare disease - Athmananda, Chandana; Narayan, Kowsthuba; Unki, Praveen (International Journal of Contemporary Pediatrics, 2022)
Von Binder described a rare congenital developmental disorder in 1962. It is a developmental disorder which is affecting the maxillary anterior region and nasal complex (nose and jaw) hence he gave the name maxillonasal dysplasia. Binder gave six classical characteristic features: arhinoid face, maxillary hypoplasia, reduced or absent nasal bridge, malformation of nasal bones, hypertrophy of turbinates with atrophy of nasal mucosa, absent frontal sinus (not compulsory). We reported a 8 years old female child presented with complaints of history of bilateral hearing loss and stuttering noticed from 2 years of age with history of delayed language and milestone development with below average academic performance and examination findings showed crescent shaped face, hypertelorism, flattened nasal bridge and ear examination findings showed low set ears. Oropharynx examination showed high arched palate, palatal scar and biﬁd uvula. Diagnostic nasal endoscopy showed bilateral hypertrophy of inferior turbinates and atrophy of nasal mucosa, pure tone audiometry done which shows B/L sensorineural hearing loss. Binder’s syndrome is a rare congenital malformation that mainly affects facial features. Treatment planning requires nose reconstruction first of all, but sometimes other medical care (such as orthodontic and orthognatic treatment) is also necessary. The timing and types of procedures involved in the treatment of patients with maxillonasal dysplasia depend on the severity of the malformation and are planned individually.